Polymer electrolyte, secondary battery and preparation method thereof
By using a non-aqueous electrolyte for thermally initiated polymerization to form a polymer electrolyte with high ionic conductivity and high thermal stability, the problem of insufficient conductivity and thermal stability of polymer electrolytes in the high-percentage state in the prior art is solved, thereby improving the safety and cycle performance of the battery.
Patent Information
- Application Number
- CN202511809673.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-03
- Publication Date
- 2026-03-17
AI Technical Summary
Existing polymer electrolytes have insufficient ion conductivity and thermal stability when used in high-percentage states, resulting in poor battery safety and cycle performance.
A non-aqueous electrolyte thermally initiated polymerization method was adopted, using borate derivatives, crosslinking agent A and crosslinking agent B, to fix the lithium-ion transport pathway through copolymerization, forming a polymer electrolyte with high ionic conductivity and high thermal stability.
It significantly improves the ion transference number and cycle life of lithium-ion batteries, while also enhancing battery safety and thermal stability, suppressing lithium dendrite growth, and improving battery safety performance at high temperatures.
Smart Images

Figure SMS_1 
Figure SMS_17 
Figure SMS_18
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, specifically relating to a polymer electrolyte, a secondary battery, and a method for preparing the same. Background Technology
[0002] Lithium-ion rechargeable batteries, through their "rocking chair" working principle, have successfully achieved efficient energy storage, becoming a key technology driving the transformation of modern society towards wireless, electric, and clean energy. Due to their high operating voltage, lack of memory effect, low self-discharge rate, and high energy density, they are widely used in portable electronic devices, energy storage, and electric vehicles. However, lithium-ion batteries contain highly reactive chemical substances, which can drastically increase safety risks under conditions of overcharging, short circuits, physical damage, and high temperatures. The electrolyte in lithium-ion batteries is typically a highly flammable organic solvent, which can trigger a combustion chain reaction under thermal runaway conditions, and the fluidity of the electrolyte can further expand the hazard range. Using solid or semi-solid electrolytes, with cross-linked polymers to "lock in" the liquid flammable components, suppressing electrolyte leakage, and reducing the severity of reactions under thermal runaway conditions are considered effective ways to improve the safety performance of lithium-ion batteries. Therefore, increasing the proportion of polymers in the electrolyte helps improve the overall high-temperature resistance of the electrolyte, thereby reducing the temperature rise of the battery under thermal runaway conditions and improving safety performance.
[0003] Polymer electrolytes often use acrylates, epoxy compounds, or amide derivatives as monomers or crosslinking agents. Although these monomers or crosslinking agents all possess a certain ionic conductivity, the transport of lithium ions within the polymer depends on the movement of polymer chain segments. Therefore, the transport efficiency of polymer electrolytes is still lower than that of pure liquid systems. Furthermore, as the polymer content increases, the overall ionic conductivity of the electrolyte decreases, significantly increasing battery polarization and leading to performance degradation.
[0004] For example, CN116454374A discloses a method for preparing a polymer electrolyte based on bis(ethylene sulfone)methane. The bis(ethylene sulfone)methane and the second monomer used are both linear structures. Under low addition levels, the resulting polymer has low crosslinking density and low strength, making it difficult to form an effective buffer under battery thermal runaway conditions. Under high addition levels (greater than 10 wt%), the amount of monomer increases, and the lithium salt and solvent in the electrolyte decrease accordingly. Since the ionic conductivity of the monomer is weaker than that of the lithium salt, the electrolyte impedance increases, and the rate capability and cycle life decrease significantly, making it difficult to meet the basic requirements of high safety and high performance for commercialization.
[0005] For example, CN120389104A discloses a composite solid electrolyte membrane with a three-dimensional interconnected network structure and its preparation method. The method involves mixing and drying PVDF-HFP, PVDF, lithium salt, initiator, solid electrolyte powder, and triazine monomers to prepare a composite solid electrolyte membrane with a three-dimensional interconnected network structure, which is then applied in the field of lithium metal batteries. This composite solid electrolyte membrane exhibits high viscosity, high flame retardancy, and high ionic conductivity. However, the ionic conductivity of the composite solid electrolyte membrane is only 5.36 × 10⁻⁶. -4 S / cm, compared to ≥6*10 for currently commercially available electrolytes. -3 The large difference in ionic conductivity between S / cm and the presence of interfacial contact issues in the organic-inorganic composite solid electrolyte prevents high-rate cycling.
[0006] For example, CN117477020A discloses a lithium-ion gel electrolyte, a lithium-ion battery, and a method for preparing the same. Due to the use of a gel electrolyte, this battery exhibits excellent electrochemical stability at the positive and negative electrode interfaces, as well as high-temperature storage performance. However, despite the good kinetic performance of this gel electrolyte, acrylonitrile is a highly toxic substance. Exposure to high temperatures can easily release highly toxic hydrogen cyanide, increasing safety risks during production and use. Summary of the Invention
[0007] The technical problem to be solved by this application is to provide a polymer electrolyte, a secondary battery and a method for preparing the same. The polymer electrolyte of this application has both high ion conductivity and high thermal stability. It can improve the safety performance of the battery under high proportion conditions, while maintaining good cycle performance.
[0008] This application provides a polymer electrolyte obtained by thermally initiated polymerization of a non-aqueous electrolyte. The non-aqueous electrolyte comprises: an organic solvent; an electrolyte salt; and a borate derivative, wherein the borate derivative accounts for 0.1%-15% of the mass of the non-aqueous electrolyte, and the borate derivative has the structure shown in general formula (I).
[0009] General Formula (I) R1, R2, and R3 are each independently selected from fluorine, chlorine, bromine, iodine, astatine, cyano, isocyanate, -N=S=O, -O-CH2-CH3, -CH2-O-CH3, alkyl groups with 1-3 carbon atoms, or haloalkyl groups with 1-3 carbon atoms; X is selected from chain alkenyl groups with 1-6 carbon atoms or chain alkynyl groups with 1-6 carbon atoms; Y is a group I metal element; crosslinking agent A accounts for 0.1%-4% of the mass of the non-aqueous electrolyte, and crosslinking agent A is a compound containing a sulfone group; crosslinking agent B has a mass ratio of (1-100):1 with crosslinking agent B being a compound containing at least three carbon-carbon double bonds; and an initiator, the mass ratio of the total mass of the borate derivative, crosslinking agent A, and crosslinking agent B to the mass of the initiator is (1000-20):1.
[0010] Furthermore, the borate derivatives account for 4%-10% of the mass of the non-aqueous electrolyte.
[0011] Furthermore, the borate derivative is selected from any one of the following structures: , , , , , , , , .
[0012] Furthermore, the general formula of crosslinking agent A is CH2=CH-(SO2)-R4-(SO2)-CH=CH2, wherein R4 is selected from -CH2-, oxygen, or any one of the following groups: , , , , , .
[0013] Furthermore, the mass of crosslinking agent A accounts for 1%-2% of the mass of the non-aqueous electrolyte.
[0014] Further, crosslinking agent B is selected from one or more of tetravinylsilane, tetramethyltetravinylcyclotetrasiloxane, octavinyl-POSS, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane, pentamethylpentavinylcyclopentasiloxane and vinyltris(trimethylsiloxane)silane, 1,3,5-triacryloylhexahydro-1,3,5-triazine, triallyl isocyanurate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate and trimethylolpropane trimethacrylate.
[0015] Furthermore, the initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, di-tert-butyl peroxide, and benzoyl tert-butyl peroxide.
[0016] Furthermore, the ratio of the total mass of the borate derivative, crosslinking agent A, and crosslinking agent B to the mass of the initiator is (40-60):1.
[0017] Furthermore, the organic solvent accounts for 30%-92% of the mass of the non-aqueous electrolyte.
[0018] Furthermore, the organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, dimethyl carbonate, fluorodimethyl carbonate, diethyl carbonate, fluorodiethyl carbonate, methyl ethyl carbonate, fluoromethyl ethyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0019] Furthermore, the molar concentration of the electrolyte salt is 0.5 mol / L to 2 mol / L.
[0020] Furthermore, the electrolyte salt is a lithium salt, which is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonyl)imide, lithium bis(oxalate)borate, lithium bis(fluorooxalate)borate, lithium perchlorate, and lithium difluorophosphate.
[0021] Furthermore, the non-aqueous electrolyte also includes additives, the mass of which accounts for 0.1%-20% of the mass of the non-aqueous electrolyte.
[0022] Furthermore, the additive is selected from one or more of the following: fluoroethylene carbonate, difluoroethylene carbonate, vinylene carbonate, ethylene ethylene carbonate, 1,3-propanesulfonate lactone, propenyl-1,3-sulfonate lactone, ethylene sulfate, propylene sulfite, mannitol carbonate sulfate, tris(trimethylsilane) phosphate, tris(trimethylsilane) phosphite, tris(trimethylsilane) borate, triethyl phosphate, trimethyl phosphate, succinate, 1,3,5-hexanetrionitrile, adiponitrile, lithium difluorooxalate borate, lithium difluorophosphate, lithium tetrafluoroborate, lithium dioxalate borate, ethoxypentafluorocyclotriphosphazene, or phenoxypentafluorocyclotriphosphazene.
[0023] This application also provides a secondary battery, comprising: a positive electrode and a negative electrode capable of absorbing and releasing metal ions, a separator, and the aforementioned non-aqueous electrolyte.
[0024] This application also provides a method for preparing the above-mentioned secondary battery, comprising: adding an electrolyte salt to an organic solvent in a glove box environment with moisture content <1ppm, such that the concentration of the electrolyte salt is within a set concentration range, adding additives and stirring evenly to obtain a basic electrolyte, adding a set mass of borate derivative, crosslinking agent A, crosslinking agent B and initiator to the basic electrolyte and mixing evenly to obtain a non-aqueous electrolyte; assembling a positive electrode, a negative electrode and a separator, injecting them into the non-aqueous electrolyte, and performing polymerization and formation at a set pressure and a set temperature.
[0025] The beneficial effects of this application are: The polymer electrolyte of this application is produced by thermally initiated polymerization of a non-aqueous electrolyte (polymerization can occur at room temperature). The non-aqueous electrolyte contains a borate derivative, crosslinking agent A, crosslinking agent B, and an initiator. The initiator is used to induce the polymerization reaction of the borate derivative, crosslinking agent A, and crosslinking agent B. The borate derivative is an alkali metal salt with high ionic conductivity. Furthermore, the anion of the borate derivative contains carbon-carbon unsaturated double bonds, and both crosslinking agent A and crosslinking agent B contain unsaturated bonds. Therefore, the anion of the borate derivative can be fixed onto the polymer backbone through copolymerization with the crosslinking agent to prepare a single-ion conductive polymer. This increases the additional lithium-ion transport pathway, significantly reduces electrolyte concentration gradient polarization, and can significantly improve ion transport number. Since the anion of the borate derivative is fixed onto the polymer backbone, there is no interfacial space charge layer caused by anion migration, resulting in more uniform lithium metal deposition. This helps suppress lithium dendrite growth and improves battery safety during cycling. Moreover, the short-chain borate derivative can regulate the mechanical strength of the polymer electrolyte without excessively sacrificing ionic conductivity, allowing the battery to balance safety and electrical performance. Crosslinker A contains sulfone groups, with a bond energy of 532 kJ / mol, which is significantly higher than the ether bond in acrylate (≈360 kJ / mol) and the CN single bond in trimethylamine (≈335 kJ / mol). Therefore, the introduction of crosslinker A can improve the thermal stability of the polymer skeleton. Crosslinker B has three or more carbon-carbon double bonds, which can form a three-dimensional branched structure, which is beneficial to increasing the crosslinking density of the polymer. Appropriately increasing the crosslinking density helps to improve battery safety. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure. All other embodiments obtained by those skilled in the art based on the described embodiments of this disclosure without creative effort are within the scope of protection of this disclosure.
[0027] Unless otherwise defined, the technical or scientific terms used herein shall have the ordinary meaning as understood by one of ordinary skill in the art to which this disclosure pertains. The terms “first,” “second,” and similar terms used in this patent application specification and claims do not indicate any order, quantity, or importance, but are merely used to distinguish different components.
[0028] Definitions of other specific words and phrases are provided throughout this disclosure. Those skilled in the art will understand that, in many, if not most, cases, such definitions apply to the prior and future use of the words and phrases thus defined.
[0029] This disclosure provides a polymer electrolyte obtained by thermally initiated polymerization of a non-aqueous electrolyte, which includes: an organic solvent, an electrolyte salt, a borate derivative, a crosslinking agent A, a crosslinking agent B, and an initiator.
[0030] The borate derivatives comprise 0.1%-15% of the mass of the non-aqueous electrolyte, and have the structure shown in general formula (Ⅰ).
[0031] General Formula (I) R1, R2, and R3 are each independently selected from fluorine, chlorine, bromine, iodine, astatine, cyano, isocyanate group, -N=S=O, -O-CH2-CH3, -CH2-O-CH3, alkyl with 1-3 carbon atoms, or haloalkyl with 1-3 carbon atoms; X is selected from chain alkenyl with 1-6 carbon atoms or chain alkynyl with 1-6 carbon atoms; and Y is a group I metal element.
[0032] Crosslinking agent A accounts for 0.1%-4% of the mass of the non-aqueous electrolyte, and crosslinking agent A is a compound containing sulfone groups.
[0033] The mass ratio of crosslinking agent B to crosslinking agent A is (1-100):1, and crosslinking agent B is a compound containing at least three carbon-carbon double bonds.
[0034] The ratio of the total mass of borate derivative, crosslinking agent A, and crosslinking agent B to the mass of initiator is (1000-20):1.
[0035] The polymer electrolyte provided in the above embodiments of this disclosure is formed by thermally initiated polymerization of a non-aqueous electrolyte (polymerization reaction can occur at room temperature). The non-aqueous electrolyte contains a borate derivative, crosslinking agent A, crosslinking agent B, and an initiator. The initiator is used to induce the polymerization reaction of the borate derivative, crosslinking agent A, and crosslinking agent B. The borate derivative is an alkali metal salt with high ionic conductivity. The anion of the borate derivative contains carbon-carbon unsaturated double bonds, and both crosslinking agent A and crosslinking agent B contain unsaturated bonds. Therefore, the anion of the borate derivative can be fixed on the polymer backbone by copolymerization with the crosslinking agent to prepare a single-ion conductive polymer, thereby increasing additional lithium-ion transport pathways, significantly reducing electrolyte concentration gradient polarization, and significantly improving ion transport number. Since the anion of the borate derivative is fixed on the polymer backbone, there is no interfacial space charge layer caused by anion migration, resulting in more uniform lithium metal deposition, which helps to suppress lithium dendrite growth and improve battery safety during cycling. Moreover, the short-chain borate derivative can regulate the mechanical strength of the polymer electrolyte without excessively sacrificing ionic conductivity, allowing the battery to balance safety and electrical performance. Crosslinker A contains sulfone groups, with a bond energy of 532 kJ / mol, which is significantly higher than the ether bond in acrylate (≈360 kJ / mol) and the CN single bond in trimethylamine (≈335 kJ / mol). Therefore, the introduction of crosslinker A can improve the thermal stability of the polymer skeleton. Crosslinker B has three or more carbon-carbon double bonds, which can form a three-dimensional branched structure, which is beneficial to increasing the crosslinking density of the polymer. Appropriately increasing the crosslinking density helps to improve battery safety.
[0036] Excessive borate derivatives result in a high proportion of conductive polymers, which reduces the solvent content in the polymer electrolyte, hindering ion migration, lowering the ion transference number, and reducing cycle life. Conversely, insufficient borate derivatives not only lead to an inadequate supply of lithium-ion transport channels, resulting in low ion transference numbers and low capacity retention of lithium-ion batteries after 800 cycles at 45°C, but also cause a decrease in the thermal stability of the polymer electrolyte due to the low proportion of conductive polymers, making it unable to pass the 140°C hot box test.
[0037] Adding too little crosslinking agent A, while beneficial for reducing impedance and increasing ion transport number, will lead to a decline in the stability of the polymer electrolyte, resulting in failure to pass the hot box test; while adding too much crosslinking agent A, while beneficial for improving the thermal stability of the polymer electrolyte, will lead to a decrease in ion transport efficiency, thus causing a deterioration in cycle performance.
[0038] If the amount of crosslinking agent B added is too low, the ion migration number of the polymer electrolyte will increase, but the thermal stability will decrease due to the low crosslinking strength. Therefore, the battery will fail the hot box safety test. If the amount of crosslinking agent B added is too high, ion migration will be hindered, and the battery cycle life will decrease significantly.
[0039] If the amount of initiator added is too low, the amount of the less active crosslinking agent A that undergoes polymerization will decrease, and some of it will not react. This will lead to some crosslinking agent A participating in the film-forming reaction, resulting in an increase in the organic component in the SEI, increased battery polarization, and a decrease in cycle life. If the amount of initiator added is too high, the rate of free radical generation at 23°C will increase. Therefore, the polymerization time will be shortened, and polymerization will occur before the non-aqueous electrolyte wetting is completed. This will affect the subsequent wetting effect of the non-aqueous electrolyte, resulting in uneven interfacial current density. Consequently, greater polarization will occur during cycling, and cycle life will decay more rapidly.
[0040] In some embodiments, the organic solvent accounts for 30%-92% of the mass of the non-aqueous electrolyte.
[0041] Preferably, the organic solvent accounts for 60%-80% of the mass of the non-aqueous electrolyte.
[0042] In some embodiments, the organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, dimethyl carbonate, fluorodimethyl carbonate, diethyl carbonate, fluorodiethyl carbonate, methyl ethyl carbonate, fluoromethyl ethyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate. For example, the organic solvent is a mixture of ethylene carbonate (EC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC). For example, the organic solvent is a single substance, propylene carbonate.
[0043] In some embodiments, the molar concentration of the electrolyte salt is 0.5 mol / L to 2 mol / L.
[0044] Preferably, the molar concentration of the electrolyte salt is 0.8 mol / L to 1.2 mol / L.
[0045] In some embodiments, the electrolyte salt is a lithium salt, selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorosulfonylimide, lithium bis(trifluoromethylsulfonylimide), lithium bis(oxalateborate), lithium di(fluorooxalateborate), lithium perchlorate, and lithium difluorophosphate. For example, the lithium salt is lithium hexafluorophosphate (LiPF6). Alternatively, the lithium salt may be both lithium hexafluorophosphate (LiPF6) and lithium difluorosulfonylimide (LiFSI).
[0046] In some embodiments, the borate derivative accounts for 4%-10% of the mass of the electrolyte. Within this range, the battery exhibits high cycle performance and ion transport number, and the polymer electrolyte demonstrates good thermal stability.
[0047] Optimally, the mass of the borate derivative accounts for 6% of the electrolyte mass. When the mass of the borate derivative is less than 6%, the number of lithium-ion transport channels provided decreases as the mass of the borate derivative decreases, thus reducing the ion transport number and cycle life. When the mass of the borate derivative is greater than 6%, the proportion of conductive polymers formed increases as the mass of the borate derivative increases, leading to a decrease in the solvent content in the polymer electrolyte, which hinders ion migration, thus reducing the ion transport number and cycle life.
[0048] In some embodiments, the borate derivative is selected from any one of those in Table 1.
[0049]
[0050] In some embodiments, the crosslinking agent A accounts for 1%-2% of the mass of the non-aqueous electrolyte. Within this range, the battery exhibits high cycle performance and ion transference number, and the polymer electrolyte demonstrates good thermal stability.
[0051] In some embodiments, the general formula of crosslinking agent A is CH2=CH-(SO2)-R4-(SO2)-CH=CH2, wherein R4 is selected from -CH2-, oxygen, or any of the following groups: , , , , , .
[0052] Crosslinking agent A is selected from any one of the compounds in Table 2. Preferably, crosslinking agent A is compound e or compound h.
[0053] Table 2.
[0054] In some embodiments, crosslinking agent B is selected from one or more of tetravinylsilane, tetramethyltetravinylcyclotetrasiloxane, octavinyl-POSS, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane, pentamethylpentavinylcyclopentasiloxane, and vinyltris(trimethylsiloxane)silane, 1,3,5-triacryloylhexahydro-1,3,5-triazine, triallyl isocyanurate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, and trimethylolpropane trimethacrylate. For example, crosslinking agent B is dipentaerythritol pentaacrylate. For example, crosslinking agent B is 1,3,5-triacryloylhexahydro-1,3,5-triazine and dipentaerythritol pentaacrylate.
[0055] Preferably, crosslinking agent B is dipentaerythritol pentaacrylate.
[0056] In some embodiments, the mass ratio of the total mass of the borate derivative, crosslinking agent A, and crosslinking agent B to the mass of the initiator is (40-60):1. Optimal, the mass ratio of the total mass of the borate derivative, crosslinking agent A, and crosslinking agent B to the mass of the initiator is 50:1. Within this range, the polymerization reaction rate is not too fast, nor is the crosslinking agent A allowed to react incompletely and participate in the film-forming reaction, thus resulting in better cycling performance of the polymer electrolyte.
[0057] In some embodiments, the initiator is selected from one or more of azobisisobutyronitrile, azobisisobutyronitrile, dimethyl azobisisobutyrate, benzoyl peroxide, di-tert-butyl peroxide, and benzoyl tert-butyl peroxide. For example, the initiator is azobisisobutyronitrile. For example, the initiator is azobisisobutyronitrile (AIBN). For example, the initiator is both azobisisobutyronitrile and benzoyl peroxide.
[0058] In some embodiments, the non-aqueous electrolyte also includes additives, the mass of which accounts for 0.1%-20% of the mass of the electrolyte.
[0059] In some embodiments, the additive is selected from one or more of the following: fluoroethylene carbonate, difluoroethylene carbonate, vinylene carbonate, ethylene ethylene carbonate, 1,3-propanesulfonate lactone, propenyl-1,3-sulfonate lactone, vinyl sulfate, propene sulfite, mannitol carbonate sulfate, tris(trimethylsilane) phosphate, tris(trimethylsilane) phosphite, tris(trimethylsilane) borate, triethyl phosphate, trimethyl phosphate, succinate, 1,3,5-hexanetrionitrile, adiponitrile, lithium difluorooxalate borate, lithium difluorophosphate, lithium tetrafluoroborate, lithium dioxalate borate, ethoxypentafluorocyclotriphosphazene, or phenoxypentafluorocyclotriphosphazene. For example, the additive may be selected from three substances: fluoroethylene carbonate (FEC), vinyl sulfate (DTD), and 1,3-propanesulfonate lactone (PS). For example, the additive may be selected from difluoroethylene carbonate.
[0060] This application also provides a secondary battery, comprising: a positive electrode and a negative electrode capable of absorbing and releasing metal ions, a separator, and the aforementioned non-aqueous electrolyte.
[0061] Specifically, the secondary battery also includes a battery casing, which can be made of aluminum-plastic film, steel, or aluminum.
[0062] Specifically, the separator includes a base film and a coating applied to the surface of the base film. The base film material can be polyethylene, polypropylene, polyacrylamide, or aramid. The coating can be a ceramic coating, which can be one or more of the following: alumina, silica, boehmite, lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, lithium lanthanum zirconium titanium oxide, lithium lanthanum zirconium niobium oxide, polyvinylidene fluoride, and methyl methacrylate.
[0063] Specifically, the positive electrode includes a positive electrode active material, a conductive agent, a binder, and a positive electrode current collector, wherein the positive electrode active material is selected from LiNi. x Co y Mn 1-x-y O2, LiNi x Co y Al 1-x-y O2 and LiFe a Mn 1-a One or more of PO4, where 0 ≤ x + y < 1 and x and y are both real numbers; a is a real number between 0 and 1. For example, the positive electrode active material is LiNi. 0.8 Co 0.1 Mn 0.1 O2. The conductive agent is selected from one or more of superconducting carbon black (Super P), acetylene black, Ketjen black, single-arm carbon nanotubes, and multi-arm carbon nanotubes. The binder is selected from one or more of polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, and polyacrylic acid. There are no particular limitations on the positive electrode current collector, and any positive electrode current collector commonly used by those skilled in the art can be used. For example, the positive electrode current collector is aluminum foil.
[0064] Specifically, the negative electrode includes a negative electrode active material, a conductive agent, a binder, and a negative electrode current collector. The negative electrode active material is selected from one or more of graphite, silicon oxide, and silicon carbon materials. For example, the negative electrode active material is 85% graphite + 15% silicon carbon. The conductive agent is selected from one or more of superconducting carbon black (Super P), acetylene black, Ketjen black, single-arm carbon nanotubes, and multi-arm carbon nanotubes. The binder is selected from one or more of polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, and polyacrylic acid. There are no particular limitations on the negative electrode current collector, and it can be any negative electrode current collector commonly used by those skilled in the art. For example, the negative electrode current collector is copper foil.
[0065] This application also provides a method for preparing the above-mentioned secondary battery, comprising: adding an electrolyte salt to an organic solvent in a glove box environment with moisture content <1 ppm, such that the concentration of the electrolyte salt is within a set concentration range; adding additives and stirring evenly to obtain a basic electrolyte; adding a set mass of borate derivative, crosslinking agent A, crosslinking agent B and initiator to the basic electrolyte and mixing evenly to obtain a non-aqueous electrolyte; assembling the positive electrode, negative electrode and separator, injecting them into the non-aqueous electrolyte, and performing polymerization and formation at a set pressure and a set temperature.
[0066] Specifically, during assembly, the positive electrode, negative electrode, and separator are stacked and aligned in the order of positive electrode sheet / separator / negative electrode sheet, and then vacuum-sealed to form a dry core.
[0067] Specifically, during the electrolyte injection and formation process, the aforementioned non-aqueous electrolyte is injected into the dry core in a glove box environment with moisture ≤1ppm, oxygen ≤1ppm, and temperature of 23±1℃. The core is then sealed and left to stand in a dry room at 23±1℃ for 48 hours. After standing, the core is formed in a pressure formation cabinet at a pressure of 0.6MPa and a temperature of 60℃ for 10 hours. It is then charged to 3.7V at a constant current and constant voltage rate of 0.2C, with a constant voltage cutoff current of 0.05C. The gas bag is then cut, vacuumed, and resealed to obtain the finished battery cell.
[0068] The present application will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. Where techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0069] Example 1 Preparation of non-aqueous electrolyte In a glove box with a moisture content of <1 ppm, ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate were mixed in a mass ratio of 1:3:1 to obtain a mixed solvent. After uniform mixing, lithium hexafluorophosphate (LiPF6, with a molar concentration of 0.8 mol / L in the non-aqueous electrolyte) and lithium difluorosulfonyl imide (LiFSI, with a molar concentration of 0.2 mol / L in the non-aqueous electrolyte) were added and completely dissolved. Then, fluoroethylene carbonate (FEC, with a mass fraction of 2 wt% in the non-aqueous electrolyte), ethylene sulfate (DTD, with a mass fraction of 1 wt% in the non-aqueous electrolyte), and 1,3-propanesulfonyl lactone (PS, with a mass fraction of 1 wt% in the non-aqueous electrolyte) were added and stirred until uniform to obtain the basic electrolyte. Then, compound 1 (6 wt% of compound 1 in the non-aqueous electrolyte), compound e (2 wt% of compound e in the non-aqueous electrolyte), dipentaerythritol pentaacrylate (4 wt% of dipentaerythritol pentaacrylate in the non-aqueous electrolyte) and azobisisobutyronitrile (AIBN, 0.24 wt% of AIBN in the non-aqueous electrolyte) were added to the base electrolyte and mixed thoroughly to obtain the non-aqueous electrolyte.
[0070] Preparation of positive electrode sheet In a dry room with humidity less than 0.1%, LiNi was placed... 0.8 Co 0.1 Mn 0.1 O2, carbon black, and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 96:2:2 and added to N-methylpyrrolidone (NMP) solvent for high-speed shear dispersion to obtain a homogenized positive electrode slurry. The positive electrode slurry was uniformly coated onto one side of an aluminum foil current collector using an automatic coating machine. After drying, the positive electrode sheet was obtained by rolling and cutting.
[0071] Preparation of negative electrode sheet A mixture of graphite and silicon carbon, single-walled carbon nanotubes, carbon black, polyacrylic acid (PAA), carboxymethyl cellulose, and styrene-butadiene rubber was mixed at a mass ratio of 96:1.1:1.1:1.2:0.6. This mixture was then added to a solvent of water and stirred until homogeneous to obtain a negative electrode slurry. The negative electrode slurry was uniformly coated onto one side of a copper foil current collector. After drying, the slurry was rolled and cut to obtain the negative electrode sheet.
[0072] Battery assembly A three-layer polymer separator with a total thickness of 20 μm was selected as the battery separator. The structure of the three-layer polymer separator is: Al2O3 ceramic / PE base film / Al2O3 ceramic, with the PE base film having a thickness of 12 μm and the two Al2O3 ceramic layers each having a thickness of 3 μm. In a dry room with humidity less than 0.1%, the separator, positive electrode, and negative electrode were stacked and aligned in the order of positive electrode / separator / negative electrode / separator / positive electrode…, stacked, tabs were welded, and vacuum-sealed to form a dry-wound core.
[0073] Injection and formation In a glove box environment with moisture ≤1ppm, oxygen ≤1ppm, and temperature of 23±1℃, a non-aqueous electrolyte is injected into the dry core, sealed, and left to stand in a dry room at 23±1℃ for 48 hours. After standing, it is formed in a pressure forming cabinet at a pressure of 0.6MPa and a temperature of 60℃ for 10 hours, charged to 3.7V at a constant current and constant voltage rate of 0.2C, with a constant voltage cutoff current of 0.05C. Then, the air bag is cut, vacuumed, and resealed to obtain the finished battery cell.
[0074] Example 2 The same descriptions as in Example 1 are omitted in Example 2. The difference between Example 2 and Example 1 is that the borate derivative is compound 7.
[0075] Example 3 The same parts as in Example 1 are omitted in Example 3. The difference between Example 3 and Example 1 is that the borate derivative is compound 8.
[0076] Example 4 The same descriptions as in Example 1 are omitted in Example 4. The difference between Example 4 and Example 1 is that crosslinking agent A is compound a.
[0077] Example 5 The same parts as in Example 1 are omitted in Example 5. The difference between Example 5 and Example 1 is that the crosslinking agent A is compound g.
[0078] Example 6 The same parts as in Example 1 are omitted in Example 6. The difference between Example 6 and Example 1 is that the crosslinking agent B is tetramethyltetravinylcyclotetrasiloxane.
[0079] Example 7 The same descriptions as in Example 1 are omitted in Example 7. The difference between Example 7 and Example 1 is that the crosslinking agent B is 1,3,5-triacryloylhexahydro-1,3,5-triazine.
[0080] Example 8 The same descriptions as in Example 1 are omitted in Example 8. The difference between Example 8 and Example 1 is that the mass fraction of the initiator is 0.48 wt%.
[0081] Example 9 The same descriptions as in Example 1 are omitted in Example 9. The difference between Example 9 and Example 1 is that the mass fraction of the initiator is 0.6 wt%.
[0082] Example 10 The same descriptions as in Example 1 are omitted in Example 10. The difference between Example 10 and Example 1 is that the mass fraction of the initiator is 0.06 wt%.
[0083] Example 11 The same descriptions as in Example 11 are omitted. The difference between Example 11 and Example 1 is that the mass fraction of the initiator is 0.3 wt%.
[0084] Example 12 The same descriptions as in Example 11 are omitted. The difference between Example 12 and Example 1 is that the mass fraction of the initiator is 0.2 wt%.
[0085] Example 13 The same descriptions as in Example 13 are omitted. The difference between Example 13 and Example 1 is that the mass fraction of the added borate derivative is 1% and the mass fraction of the added initiator is 0.14%.
[0086] Example 14 The same descriptions as in Example 14 are omitted. The difference between Example 14 and Example 1 is that the mass fraction of the added borate derivative is 2% and the mass fraction of the added initiator is 0.16%.
[0087] Example 15 The same descriptions as in Example 15 are omitted. The difference between Example 15 and Example 1 is that the mass fraction of the added borate derivative is 4% and the mass fraction of the added initiator is 0.2%.
[0088] Example 16 The same descriptions as in Example 16 are omitted. The difference between Example 16 and Example 1 is that the mass fraction of the added borate derivative is 10% and the mass fraction of the added initiator is 0.32%.
[0089] Example 17 The same descriptions as in Example 17 are omitted. The difference between Example 17 and Example 1 is that the mass fraction of the added borate derivative is 15% and the mass fraction of the added initiator is 0.42%.
[0090] Example 18 The same descriptions as in Example 18 are omitted. The difference between Example 18 and Example 1 is that the mass fraction of crosslinking agent A added is 0.5%.
[0091] Example 19 The same descriptions as in Example 19 are omitted. The difference between Example 19 and Example 1 is that the mass fraction of crosslinking agent A added is 1%. Example 20 The same parts as in Example 1 are omitted. The difference between Example 20 and Example 1 is that the mass fraction of crosslinking agent A added is 4%.
[0092] Example 21 The same parts as in Example 1 are omitted. The difference between Example 21 and Example 1 is that the mass fraction of crosslinking agent A added is 6%.
[0093] Example 22 The same parts as in Example 1 are omitted in Example 21. The difference between Example 22 and Example 1 is that the mass fraction of the added crosslinking agent B is 2%.
[0094] Example 23 The same parts as in Example 1 are omitted in Example 23. The difference between Example 23 and Example 1 is that the mass fraction of crosslinking agent B added is 10%.
[0095] Example 24 The same parts as in Example 1 are omitted in Example 24. The difference between Example 24 and Example 1 is that the mass fraction of the added crosslinking agent B is 0.5%.
[0096] Example 25 The same parts as in Example 1 are omitted in Example 25. The difference between Example 25 and Example 1 is that the mass fraction of crosslinking agent B added is 15%.
[0097] Example 26 The same descriptions as in Example 1 are omitted in Example 26. The difference between Example 26 and Example 1 is that the mass fraction of compound 1 added is 0.1%, the mass fraction of dipentaerythritol pentaacrylate added is 10%, and the mass fraction of AIBN added is 0.242%.
[0098] Example 27 The same descriptions as in Example 1 are omitted in Example 27. The difference between Example 27 and Example 1 is that the mass fraction of compound e added is 0.1%, the mass fraction of dipentaerythritol pentaacrylate added is 10%, and the mass fraction of AIBN added is 0.33%.
[0099] Example 28 The same descriptions as in Example 1 are omitted in Example 26. The difference between Example 26 and Example 1 is that the organic solvent is EMC; the lithium salt is LiFSI, and the molar concentration of the added LiFSI is 1.0 mol / L; the additive is FEC, and the mass fraction of the added FEC is 5%.
[0100] Example 29 The same descriptions as in Example 1 are omitted in Example 27. The difference between Example 27 and Example 1 is that the organic solvent is EMC and EC, and the mass ratio of EMC and EC is 2:3; the lithium salt is LiPF6; the molar concentration of the added LiFSI is 1.0 mol / L; the additive is DTD, and the mass fraction of the added DTD is 5%.
[0101] Comparative Example 1 The same descriptions as in Comparative Example 1 and Example 1 are omitted. The difference between Comparative Example 1 and Example 1 is that in the preparation of the non-aqueous electrolyte, borate derivatives, crosslinking agent A, crosslinking agent B, and initiator were not added. In the liquid injection and formation process, after "after standing, it is passed through a pressure formation chamber", the step of "forming at a pressure of 0.6 MPa and a temperature of 60°C for 10 hours" is omitted.
[0102] Comparative Example 2 The same descriptions as those in Comparative Example 2 and Example 1 are omitted. The difference between Comparative Example 2 and Example 1 is that no crosslinking agent A was added during the preparation of the non-aqueous electrolyte, and the mass fraction of the initiator added was 0.2%.
[0103] Comparative Example 3 The same descriptions as those in Comparative Example 3 and Example 1 are omitted. The difference between Comparative Example 3 and Example 1 is that no crosslinking agent B was added during the preparation of the non-aqueous electrolyte, and the mass fraction of the initiator added was 0.16%.
[0104] Comparative Example 4 The same descriptions as those in Comparative Example 4 and Example 1 are omitted. The difference between Comparative Example 4 and Example 1 is that no borate derivatives were added during the preparation of the non-aqueous electrolyte.
[0105] Comparative Example 5 The same descriptions as those in Comparative Example 5 and Example 1 are omitted. The difference between Comparative Example 5 and Example 1 is that in the preparation of the non-aqueous electrolyte, the added borate derivative is replaced with lithium hexafluorophosphate.
[0106] Comparative Example 6 The same descriptions as those in Comparative Example 6 and Example 1 are omitted. The difference between Comparative Example 6 and Example 1 is that lithium hexafluorophosphate and lithium difluorosulfonylimide in the lithium salt are replaced with borate derivatives, and the mass fraction of the added initiator is 0.52%.
[0107] The amounts of each substance added in Examples 1 to 18 and Comparative Examples 1 to 6 are shown in Table 3.
[0108] Table 3.
[0109] Electrochemical performance testing Electrochemical performance tests were conducted on the batteries of Examples 1 to 29 and Comparative Examples 1 to 6.
[0110] 1. High-temperature cycling performance test In a constant temperature chamber at 45°C, the lithium secondary batteries prepared in Examples 1 to 29 and Comparative Examples 1 to 6 were charged at a constant current rate of 1C to 4.2V, then charged at a constant voltage rate to a current rate of 0.05C, and then discharged at a constant current rate of 1C to 2.5V. This charge / discharge cycle was performed, and the capacity retention rate of the batteries after 800 cycles was recorded. The test results of Examples 1 to 18 and Comparative Examples 1 to 6 are shown in Table 2.
[0111] 2. Ion transport number test In a glove box environment with moisture ≤0.5ppm, oxygen ≤0.5ppm, and temperature of 23±1℃, a lithium sheet was placed in the positive electrode shell of a coin cell, a non-aqueous electrolyte was added, a separator disc was placed in, another non-aqueous electrolyte was added, the lithium sheet was placed in, and finally the negative electrode shell was placed in and sealed. After standing for 5 hours, it was placed in a constant temperature oven at 60℃ for 10 hours (to allow the non-aqueous electrolyte to polymerize), and then left to stand until the battery temperature dropped to room temperature. A constant voltage (ΔV) of 10 mV was applied through a symmetrical cell (Li|electrolyte|Li), and the initial current (I0) and steady-state current (I0) were recorded. ssThe impedance R0 and Rss of the symmetric cell before and after polarization were measured using an electrochemical workstation, along with the lithium-ion transference number t. Li+ =I ss *(△V-R0I0) / (I0*(△VR ss I ss The test results of Examples 1 to 18 and Comparative Examples 1 to 6 are shown in Table 4.
[0112] 3. 140℃ Hot Box Test A fully charged battery (SOC=100%, upper limit voltage 4.2V) was placed in a constant temperature chamber, and the temperature was increased to 140°C at a rate of 5°C / min and maintained for 60 minutes. The battery status was observed, and the battery was considered to have passed the test if it did not catch fire or explode. The test results of Examples 1 to 18 and Comparative Examples 1 to 6 are shown in Table 4.
[0113] 4. Non-aqueous electrolyte standing test at room temperature The non-aqueous electrolyte was placed in a 20ml glass bottle, which was then placed in a glove box at 23±1℃. The time taken for the electrolyte to go from transparent to the start of polymerization was observed and recorded. The test results of Examples 1 to 18 and Comparative Examples 1 to 6 are shown in Table 4.
[0114] The electrochemical test data of the full cells in Examples 1 to 29 and Comparative Examples 1 to 6 are shown in Table 4.
[0115] Table 4.
[0116] According to the data in Table 4, the non-aqueous electrolyte in Comparative Example 1 did not contain borate derivatives, crosslinking agent A, crosslinking agent B, and initiator. The lithium secondary battery prepared from it could not pass the 140℃ hot box test, and the lithium secondary battery had low capacity retention and low ion transference number after 800 cycles at 45℃.
[0117] In Comparative Example 2, the absence of crosslinking agent A in the non-aqueous electrolyte led to a decrease in the thermal stability of the prepared lithium secondary battery, which failed the 140°C hot box test.
[0118] In Comparative Example 3, the non-aqueous electrolyte lacked crosslinking agent B, resulting in a reduced crosslinking density and failure to pass the 140℃ hot box test.
[0119] In Comparative Example 4, the borate derivative was replaced with dipentaerythritol pentaacrylate. Due to the sufficient polymer crosslinking density, it was able to pass the 140°C hot box test. However, the non-aqueous electrolyte did not contain the borate derivative and could not provide anions for the borate derivative, resulting in a low ion transference number and deterioration of kinetics. The lithium secondary battery had a low capacity retention rate after 800 cycles at 45°C.
[0120] In Comparative Example 5, lithium hexafluorophosphate was used to replace the borate derivative. Although both are lithium salts, appropriately increasing their content is beneficial for improving the ion transference number. However, lithium hexafluorophosphate anions can move freely, increasing concentration gradient polarization, thus the ion transference number is not as high as in Example 1. Due to the low total proportion of monomer and crosslinking agent, the resulting polymer layer has insufficient strength and therefore cannot pass the 140°C hot box test.
[0121] In Comparative Example 6, the non-aqueous electrolyte contained no lithium salt, and the lithium salt was completely replaced by boric acid derivatives. Due to the lack of lithium salt with high ionic conductivity and the excessive total amount of polymer monomers and crosslinking agents, the ion transference number decreased, leading to increased polarization. As a result, the capacity retention of the lithium secondary battery decreased significantly after 800 cycles at 45°C.
[0122] According to the data in Examples 1 and 8-12, when the mass ratio of the total mass of borate derivatives, crosslinking agent A, and crosslinking agent B to the mass of the initiator is 40-60, the lithium secondary battery passes the 140°C hot box test, and the ion transport number and capacity retention rate of the lithium secondary battery after 800 cycles at 45°C are both optimal. When the mass ratio of the total mass of borate derivatives, crosslinking agent A, and crosslinking agent B to the mass of the initiator is less than 40, the capacity retention rate of the lithium secondary battery after 800 cycles at 45°C decreases as the ratio decreases. When the mass ratio of the total mass of borate derivatives, crosslinking agent A, and crosslinking agent B to the mass of the initiator is greater than 60, the capacity retention rate of the lithium secondary battery after 800 cycles at 45°C decreases. This indicates that if the amount of initiator added is too low, the amount of the less active crosslinking agent A that undergoes polymerization will decrease, resulting in some of it not reacting. This leads to some crosslinking agent A participating in the film-forming reaction, increasing the organic component in the SEI, increasing battery polarization, and decreasing cycle life. If the amount of initiator added is too high, the rate of free radical generation at 23°C will increase, thus shortening the polymerization time. Polymerization will occur before the non-aqueous electrolyte wetting is complete, affecting the subsequent wetting effect of the non-aqueous electrolyte. This will lead to uneven interfacial current density, resulting in greater polarization during cycling and accelerating cycle life decay.
[0123] According to the data from Examples 1, 13-17, Example 26, Comparative Example 4, and Comparative Example 5, based on the data from Example 13 and Comparative Example 5, when the content of crosslinking agent B is 4% and the content of boric acid derivative is 0wt% and 1wt%, respectively, the lithium secondary battery fails the 140°C hot box test due to low ion transport number. The lithium secondary battery also exhibits low capacity retention after 800 cycles at 45°C. This indicates that insufficient borate derivative quality leads to a decrease in electrolyte ion transport number, resulting in low capacity retention after 800 cycles at 45°C. Furthermore, the low proportion of conductive polymer reduces the thermal stability of the polymer electrolyte, causing the lithium secondary battery to fail the 140°C hot box test. However, according to the data from Example 26 and Comparative Example 4, when there is no boric acid derivative or the content of boric acid derivative is 0.1wt% and the content of crosslinking agent is 10%, the lithium secondary battery passes the 140°C hot box test. However, due to the low or absent content of boric acid derivative, the provided lithium ion transport channels are insufficient, leading to a decrease in ion transport number and cycle life. According to data from Examples 14-17, when the content of crosslinking agent B was 4% and the content of boric acid derivative increased to 2 wt%, the lithium secondary battery passed the 140°C hot box test, the ion migration number increased, and the capacity retention rate of the lithium secondary battery after 800 cycles at 45°C increased. When the content of boric acid derivative continued to rise to 6 wt%, the ion migration number reached its maximum, and the capacity retention rate of the lithium secondary battery after 800 cycles at 45°C reached its maximum. As the content of boric acid derivative continued to rise, the ion migration number began to decrease, and the capacity retention rate of the lithium secondary battery after 800 cycles at 45°C began to decrease. When the content of boric acid derivative rose to 10 wt%, the capacity retention rate of the lithium secondary battery after 800 cycles at 45°C decreased to 80.85%. When the content of boric acid derivative rose to 15 wt%, the capacity retention rate of the lithium secondary battery after 800 cycles at 45°C had decreased to 70.66%. This indicates that within a certain range, as the content of borate derivatives increases, both the ion transport number and the capacity retention of the lithium-ion battery after 800 cycles at 45°C increase. After reaching a maximum value, both the ion transport number and the capacity retention decrease as the content of borate derivatives decreases. The increase in ion transport number and capacity retention within a certain range is due to the increased lithium-ion transport channels provided by the borate derivatives. However, beyond a certain range, the increased mass of borate derivatives leads to a decrease in the solvent content in the polymer electrolyte, hindering ion migration and thus reducing the ion transport number and cycle life.
[0124] According to the data from Examples 1, 18-21, 27 and Comparative Example 2, when the content of crosslinking agent B is less than 10% and the content of crosslinking agent A is 0 wt% and 0.5 wt%, although the ion transference number and the capacity retention rate of the lithium secondary battery after 800 cycles at 45°C are both high, the lithium secondary battery fails the 140°C hot box test. When the content of crosslinking agent A increases to 1 wt%, the lithium secondary battery passes the 140°C hot box test, and the ion transference number and the capacity retention rate of the lithium secondary battery after 800 cycles at 45°C are both high. When the content of crosslinking agent A is in the range of 1 wt%-4 wt%, the ion transference number and the capacity retention rate of the lithium secondary battery after 800 cycles at 45°C are both high. However, when the content of crosslinking agent A continues to increase to 4 wt%, although the lithium secondary battery passes the 140°C hot box test, the ion transference number and the capacity retention rate of the lithium secondary battery after 800 cycles at 45°C both decrease. This indicates that while adding too little crosslinking agent A can reduce impedance and increase ion transport number, it also leads to a decline in the stability of the polymer electrolyte, causing it to fail the hot-box test. Conversely, adding too much crosslinking agent A can improve the thermal stability of the polymer electrolyte, but it results in a decrease in ion transport efficiency, thus deteriorating cycle performance. However, as shown in Example 27, when the content of crosslinking agent B is 10 wt%, although the content of crosslinking agent A is 0.1 wt%, the high content of crosslinking agent B results in a high polymer crosslinking density, allowing the lithium secondary battery to still pass the hot-box test. However, due to the low content of crosslinking agent A, which has high thermal stability, the capacity retention rate and ion transport number decrease after 800 cycles at 45°C.
[0125] Based on the data from Examples 1, 22-25, and Comparative Example 3, it can be seen that when there is no crosslinking agent B, the mass ratio of crosslinking agent B to crosslinking agent A is 1:4, and the content of crosslinking agent B is less than 2%, although the ion transference number and the capacity retention rate of the lithium secondary battery after 800 cycles at 45°C are both high, the lithium secondary battery fails the 140°C hot box test. When the mass ratio of crosslinking agent B to crosslinking agent A increases to 1:1, the lithium secondary battery passes the 140°C hot box test, and the ion transference number and capacity retention rate after 800 cycles at 45°C are high. The crosslinking agent B and crosslinking agent A maintained high ion mobility and high capacity retention of the lithium secondary battery after 800 cycles at 45°C when the mass ratio of crosslinking agent B to crosslinking agent A was between 1:1 and 5:1. However, when the mass ratio of crosslinking agent B to crosslinking agent A increased to 5:1, both the ion mobility and capacity retention of the lithium secondary battery after 800 cycles at 45°C decreased. When the mass ratio of crosslinking agent B to crosslinking agent A increased to 7.5:1, both the ion mobility and capacity retention of the lithium secondary battery after 800 cycles at 45°C showed a significant decrease. This indicates that if the amount of crosslinking agent B added is too low, the ion mobility of the polymer electrolyte will increase, but due to the low crosslinking strength, the thermal stability will decrease, and therefore the battery will fail the hot box safety test. If the amount of crosslinking agent B added is too high, ion migration will be hindered, and therefore the battery cycle life will decrease significantly.
[0126] Compared to Example 1, in Example 2, the fluorine atom bonded to the boron atom in the borate derivative was replaced with a methyl group. The cycle retention rate of the prepared secondary battery at 45°C was reduced. The main reason is that the methyl group is a weak electron-donating group, which can reduce the electron deficiency of the boron center, leading to the localization of the anion charge and enhancing the association with Li⁺, thereby reducing the ion transference number. On the other hand, fluorine has a very strong electron-withdrawing ability, which can highly delocalize the negative charge and promote the dissociation of Li⁺, thus resulting in a higher ion transference number.
[0127] Compared with Example 2, in Example 3, the alkyl group connected to the boron atom in the borate derivative was changed from methyl to ethyl, and the side chain volume was further increased, resulting in a decrease in ion transference number. Therefore, the cycle retention rate of the prepared secondary battery at 45°C declined.
[0128] Compared to Example 1, in Example 4, compound e was replaced with compound a in crosslinking agent A. In Example 5, compared to Example 1, compound e was replaced with compound g in crosslinking agent A. The secondary batteries prepared in Examples 1, 4, and 5 showed similar cycle retention rates and ion transport numbers at 45°C, indicating that the different structures of R4 in crosslinking agent A (CH2=CH-(SO2)-R4-(SO2)-CH=CH2) have little impact on the performance of the polymer electrolyte.
[0129] Compared to Example 1, in Example 6, the crosslinking agent B was changed from dipentaerythritol pentaacrylate to tetramethyltetravinylcyclotetrasiloxane. Due to the low intrinsic ionic conductivity of the siloxane structure, the ion transference number of the resulting polymer electrolyte decreased, leading to a reduction in the capacity retention of the prepared lithium secondary battery after 800 cycles at 45°C. In Example 7, compared to Example 1, the crosslinking agent B was changed from dipentaerythritol pentaacrylate to 1,3,5-triacryloylhexahydro-1,3,5-triazine. Since 1,3,5-triacryloylhexahydro-1,3,5-triazine contains carbonyl and nitrogen heterocycles and has a lower oxygen content than dipentaerythritol pentaacrylate, the capacity retention of the prepared lithium secondary battery after 800 cycles at 45°C decreased.
[0130] The text in this disclosure is provided by way of example only to aid in understanding this disclosure. It should not be construed as limiting the scope of this disclosure in any way. Although certain embodiments and examples have been provided, it will be clear to those skilled in the art, based on the content disclosed herein, that changes can be made to the illustrated embodiments and examples without departing from the scope of this disclosure.
[0131] Although this disclosure has been described with reference to exemplary embodiments, various changes and modifications may be suggested to those skilled in the art. This disclosure is intended to cover such changes and modifications that fall within the scope of the appended claims.
[0132] Nothing described in this disclosure should be construed as implying that any particular element, step, or function is an essential element that must be included within the scope of the claims. The scope of the patent subject matter is defined only by the claims.
Claims
1. A polymer electrolyte, characterized in that: the polymer electrolyte is obtained by thermal initiation polymerization of a non-aqueous electrolyte solution, the non-aqueous electrolyte solution comprises: an organic solvent; an electrolyte salt; a borate derivative, the mass of the borate derivative accounts for 0.1%-15% of the mass of the non-aqueous electrolyte solution, the borate derivative has a structure shown in a general formula (I), the general formula (I) is: wherein, R1, R2, R3 are each independently selected from fluorine, chlorine, bromine, iodine, astatine, a cyano group, an isocyanate group, -N=S=O, -O-CH2-CH3, -CH2-O-CH3, an alkyl group with 1-3 carbon atoms or a halogenated alkyl group with 1-3 carbon atoms, X is selected from a chain alkenyl group with 1-6 carbon atoms or a chain alkyne group with 1-6 carbon atoms, Y is a first main group metal element; a crosslinking agent A, the mass of the crosslinking agent A accounts for 0.1%-4% of the mass of the non-aqueous electrolyte solution, the crosslinking agent A is a compound containing a sulfonyl group; a crosslinking agent B, the mass ratio of the crosslinking agent B to the crosslinking agent A is (1-100):1, the crosslinking agent B is a compound containing at least three carbon-carbon double bonds; and an initiator, the mass ratio of the sum of the mass of the borate derivative, the crosslinking agent A, the crosslinking agent B to the mass of the initiator is (1000-20):
1. 2.The polymer electrolyte according to claim 1, characterized in that: the mass of the borate derivative accounts for 4%-10% of the mass of the non-aqueous electrolyte solution. 3.The polymer electrolyte according to claim 1, characterized in that: the borate derivative is selected from any one of the following structures: 4.The polymer electrolyte according to claim 1, characterized in that: the general formula of the crosslinking agent A is CH2=CH-(SO2)-R4-(SO2)-CH=CH2, wherein, R4 is selected from -CH2-, oxygen or any one of the following groups: 5.The polymer electrolyte according to claim 1, characterized in that: the mass of the crosslinking agent A accounts for 1%-2% of the mass of the non-aqueous electrolyte solution. 6.The polymer electrolyte according to claim 1, characterized in that: the crosslinking agent B is selected from one or more of tetraethenylsilane, tetramethyltetraethenylcyclotetrasiloxane, octavinyl-POSS, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane, pentamethylpentavinylcyclopentasiloxane and vinyltris(trimethylsiloxy)silane, 1,3,5-triacryloylhexahydro-1,3,5-triazine, triallylisocyanurate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate and trimethylolpropane trimethacrylate. 7.The polymer electrolyte according to claim 1, characterized in that: the initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptyl nitrile, dimethyl azobis isobutyrate, di-tert-butyl peroxide, benzoyl peroxide and benzoyl peroxide tert-butyl ester. 、 、 、 、 、 、 、 、 。 、 、 、 、 、 。 8.The polymer electrolyte according to claim 1, characterized in that, a ratio of a total mass of the borate derivative, the crosslinking agent A, the crosslinking agent B to a mass of the initiator is (40-60) :
1. 9.The polymer electrolyte according to claim 1, characterized in that, a mass of the organic solvent accounts for 30%-92% of a mass of the non-aqueous electrolyte. 10.The polymer electrolyte according to claim 1, characterized in that, the organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, bisfluoroethylene carbonate, dimethyl carbonate, fluorodimethyl carbonate, diethyl carbonate, fluorodiethyl carbonate, methyl ethyl carbonate, fluoromethyl ethyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate and butyl propionate. 11.The polymer electrolyte according to claim 1, characterized in that, a molar concentration of the electrolyte salt is 0.5mol / L-2mol / L. 12.The polymer electrolyte according to claim 1, characterized in that, the electrolyte salt is a lithium salt, and the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisfluorosulfonylimide, lithium bis-trifluoromethylsulfonylimide, lithium bis-oxalato-borate, lithium bis-fluoro-oxalato-borate, lithium perchlorate and lithium difluorophosphate. 13.The polymer electrolyte according to claim 1, characterized in that, the non-aqueous electrolyte further comprises an additive, and a mass of the additive accounts for 0.1%-20% of a mass of the non-aqueous electrolyte. 14.The polymer electrolyte according to claim 13, characterized in that, the additive is selected from one or more of fluoroethylene carbonate, bisfluoroethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, propenyl-1,3-sultone, ethylene sulfate, propylene sulfite, mannitol carbonate sulfate, tris (trimethylsilyl) phosphate, tris (trimethylsilyl) phosphite, tris (trimethylsilyl) borate, triethyl phosphate, trimethyl phosphate, butanedinitrile, 1,3,5-hexanetricarbonitrile, hexanedinitrile, lithium bis-fluoro-oxalato-borate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bis-oxalato-borate, ethoxy-pentafluorocyclotriphosphazene and phenoxy-pentafluorocyclotriphosphazene.
15. A secondary battery characterized by comprising: including: a positive electrode and a negative electrode capable of occluding and releasing metal ions, a separator and the polymer electrolyte according to any one of claims 1-14. 16.A preparation method of the secondary battery according to claim 15, characterized in that: in a glove box environment with moisture <1ppm, an electrolyte salt is added to an organic solvent so that a concentration of the electrolyte salt is within a set concentration range, an additive is added and stirred to obtain a base electrolyte, a borate derivative, a crosslinking agent A, a crosslinking agent B and an initiator are added to the base electrolyte in a set mass and mixed to obtain a non-aqueous electrolyte; after assembling a positive electrode, a negative electrode and a separator, the non-aqueous electrolyte is injected, and polymerization and formation are performed at a set pressure and a set temperature.
Citation Information
Patent Citations
Polymer electrolyte based on bis (vinyl sulfuryl) methane and preparation method thereof
CN116454374A
Lithium ion gel-state electrolyte, lithium ion battery and preparation method of lithium ion gel-state electrolyte
CN117477020A
Composite solid electrolyte membrane with three-dimensional intertransmission network structure and preparation method of composite solid electrolyte membrane
CN120389104A
Cited By
Battery monomer and manufacturing method thereof, battery device, power utilization device and energy storage device
CN121885784A